A diversified vertebrate ichnite fauna from the Dasheng Group (Lower Cretaceous) of southeast Shandong Province, China. (16th March 2019) - Xing, Lida; Lockley, Martin G.; Zhang, Junqiang; Romilio, Anthony; Klein, Hendrik; Wang, Yan; Tang, Yonggang; Burns, Michael E.; Wang, Xiaoli
Abstract: The Qingquan dinosaur tracksite, from the Lower Cretaceous Dasheng Group, Shandong Province, China adds to the growing record of saurischian-dominated ichnofaunas of the region. The site reveals the presence of avian theropods ( Koreanaornis ) and non-avian theropods tentatively referred to Jialingpus . Sauropod tracks are referred to Brontopodus . One site shows evidence of extensive trampling attributable to sauropods and theropods that moved in the same westerly direction, though not necessarily at exactly the same time. This site is reminiscent of the famous Davenport Ranch site in Texas which has provoked much debate about the herding behavior of sauropods as a defense strategy against theropod predators.